Liberia : Fourth Review Under the Three; Year Arrangement Under the Extended Credit Facility, Request for Modification of Performance Criteria, and Financing Assurances Review; Staff Report; Informational Annex; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Liberia. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
Political pressure for faster delivery of tangible economic results has mounted against a backdrop of slower-than-expected economic growth, job losses in some sectors, and delays in infrastructure provision. Macroeconomic performance weakened in 2009 owing to the global recession, but tentative signs of a turnaround have emerged. Banking sector capitalization improved, though profitability remains low. FY2010 budget execution is broadly on track despite resource shortfalls. Medium-term prospects are favorable based on foreign investment commitments and continued donor support for rebuilding infrastructure and institutions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet